2008
DOI: 10.1051/0004-6361:200809815
|View full text |Cite
|
Sign up to set email alerts
|

Vertical temperature profile and mesospheric winds retrieval on Mars from CO millimeter observations

Abstract: Aims.We have recorded high spectral resolution spectra and derived precise atmospheric temperature profiles and wind velocities in the atmosphere of Mars. We have compared observations of the planetary mean thermal profile and mesospheric wind velocities on the disk, obtained with our millimetric observations of CO rotational lines, to predictions from the Laboratoire de Météorologie Dynamique (LMD) Mars General Circulation Model, as provided through the Mars Climate Database (MCD) numerical tool. Methods. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
(44 reference statements)
1
13
0
Order By: Relevance
“…Within each layer, the atmospheric temperature, pressure, and volume mixing ratio of carbon monoxide were assumed to be constant. The surface continuum emission was mod- eled as black-body emission using a temperature distribution falling off towards the edge of the apparent disk according to T (α) = T 0 × (1 − 0.2 × (1 − cos(α))), with α running from 0 -90 • across the apparent disk (see also Cavalié et al 2008). The diskaveraged emission was obtained by integrating over the apparent disk using sixty four concentric rings distributed unevenly over the disk and the limb region.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Within each layer, the atmospheric temperature, pressure, and volume mixing ratio of carbon monoxide were assumed to be constant. The surface continuum emission was mod- eled as black-body emission using a temperature distribution falling off towards the edge of the apparent disk according to T (α) = T 0 × (1 − 0.2 × (1 − cos(α))), with α running from 0 -90 • across the apparent disk (see also Cavalié et al 2008). The diskaveraged emission was obtained by integrating over the apparent disk using sixty four concentric rings distributed unevenly over the disk and the limb region.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Fig. 14 presents a synthetic view of all these wind measurements, except for the 2001 and 2005 data, which are described by Cavalié et al (2008). Single-dish observations make use of a "point-by-point" mapping technique, in which spectra are accumulated on a sequence of individual beam positions.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…References: a Lellouch et al 1991a, b Gillet and Lellouch 1994, c Jegou (2003, d Cavalié et al, 2008. …”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Larger‐scale winds such as tidal oscillations are thought to be the dominant modes of the motion in the thermosphere of Mars [ Bougher et al , 2001]. Cavalie et al [2008] have reported that zonal winds are representative of the Martian seasons. One needs to know what mode of the zonal wind predominates in the troposphere of Mars.…”
Section: Objectivementioning
confidence: 99%